Efek Gel Ekstrak Daun Sirsak (Annona Muricata L.) sebagai Agen Antiulkus pada Tikus Diabetes Induksi Aloksan : Studi Histologi - Magdalena Tiara V Manihuruk; Muhammad Yunus; Asyrun Alkhairi Lubis (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Diabetes Melitus is a chronic hyperglikemia codition that can impair wound healing due to distrupted tissue regeneration and alterrations in skin histological structure. Burn wounds under diabetic conditions tend to experience delayed healing as a result of decreased fibroblast activity, suboptimal collagen formation, and impaired angiogenesis. Soursoup leaves (Annona muricata l.) are known to contain bioactive compounds that may support the wound healing process. This study aimed to evaluate the effectiviness of soursoup leaf extract gel on burn wound healing in alloxan-induced diabetic rats through histological into six groups, consisting of a normal control, negative control, positive control ( Bioplacenton ), and treatment groups receiving soursoup leaf extract gel at concentration of 5%,10% and 15%. The observed parameters included the percentage of wound healing and histological festures of skin tissue, namely fibroblast count, collagen density and capillary formation. The result showed that administration of soursoup leaf increased number of fibroblast, improved collagen formation and enchanced skin tissue regeneration. Soursoup leaf extract gel has the potency accelerate burn wound heaing in alloxan-induced diabetic rats through improvement of skin tissue histological structure.